Research and implementation on optical wireless communication technologies - Chen, Xing (2025)
Continuous global growth and increasing demand for wireless communication cause a shortage of radio frequency (RF) spectrum. Optical wireless communication (OWC) is expected to alleviate this looming spectrum crisis. Among OWC technologies, free space optic (FSO) and visible light communication (VLC) have rapidly become a research hot spot because of significant development and application prospects.